(untitled) (Eurasian Research Bulletin, 2022)
In this article, the new educational system introduced in our country, i.e. the improvement of the inclusive education system, and the introduction of this educational system in pre-school educational organizations, new decisions and decrees have been adopted in order to develop the inclusive education system. , it is said that tasks have been assigned.